Optimizing nitrogen application position to change root distribution in soil and regulate maize growth and yield formation in a wide–narrow row cropping system: pot and field experiments - Zhou, Shiyong; Xia, Pan; Chen, Junping; Xiong, Qijiao; Li, Guanhan; Tian, Jingyi; Wu, Bozhi; Zhou, Feng (Frontiers in Plant Science, 2024)
The wide-and narrow-row cropping technology used for maize has the advantages of protecting cultivated soil and improving the population structure in maize fields. However, the relationship between nitrogen application position and root interactions has not been determined.Through pot and field experiments, we evaluated the effects of two nitrogen application positions ((narrow row nitrogen application (RC) and wide row nitrogen application (RN)) and two nitrogen application regimens ((high nitrogen(HN) and low nitrogen(LN)) on root growth and yield composition of wide-narrow row maize during the flowering and harvest stages.In field experiments, RC increased the biomass, length and surface area of competing roots (narrow-row roots, CR) at the flowering stage. The yield and agronomic efficiency of N(AEN) and partial factor productivity of N(PFPN) were increased by RN compared to RC under HN, However, the AEN under LN was significantly lower; There was no significant effect on maize growth and biomass allocation at the same level of application of N. At the flowering stage, the results of CR and non-competing roots (wide-row roots, NCR) was consistent under pot experiments and the field experiments, and the yield under RN was also higher than that under RC, although the difference was not significant. Furthermore, according to the principal component analysis and correlation analysis, the competing roots were the main factor influencing yield and AEN. In conclusion, our study showed that RN is a useful fertilization method to improve overall productivity. All in all, how roots coordinate neighbors and nitrogen spatial heterogeneity is a complex ecological process, and its trophic behavior deserves further study.